Emotional Deprivation And Its Relationship To Hyperactivity Among Primary School Pupils - Ashwak Saber Nasser (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aimed to identify emotional deprivation and hyperactivity and the relationship between them among primary school pupils. The sample of the current research was limited to (100) male and female sixth-grade students selected in a random way. The researcher has prepared two tools, namely, the emotional deprivation scale, which consisted of (28) items and the hyperactivity scale and this consisted of (30) items. For these two scales, the researcher also extracted the psychometric characteristics of honesty, stability and discrimination of the items. After applying the scales, the results showed that there are statistically significant differences between the mean of the sample and the hypothetical mean and in favour of the sample mean on the emotional deprivation scale and the hyperactivity scale. There is also a significant relationship between emotional deprivation and hyperactivity.